EBF recommendation on practical management of critical reagents for PK ligand-binding assays. (18th September 2018) - Pihl, Susanne; van der Strate, Barry WA; Golob, Michaela; Vermet, Laurent; Jaitner, Birgit; Goodman, Joanne; Fjording, Marianne Scheel; Timmerman, Philip
Critical reagents play a crucial role in ligand-binding assays; the robustness and reliability of an assay is defined by the quality and long-term availability of these reagents. However, neither regulatory guidelines nor relevant scientific papers provide clear directions for set-up, life cycle management and, more importantly, the acceptance criteria required for the testing of the critical reagents for pharmacokinetic, biomarker and immunogenicity assays. The ambiguity from current guidelines can be a challenge for the bioanalytical community. Members of the European Bioanalysis Forum community undertook a more pragmatic approach on how to assess the impact of critical reagents. In this paper, a review and corresponding gap analysis of the current guidelines and relevant papers will be provided as well as decision trees proposed for lot-to-lot changes of critical reagents for pharmacokinetic assays.